Well-defined molecular magnesium hydride clusters: Relationship between size and hydrogen-elimination temperature - Intemann, Julia; Spielmann, Jan; Sirsch, Peter; Harder, Sjoerd (Chemistry - A European Journal, 2013)
A new tetranuclear magnesium hydride cluster, [NN-(MgH) ], which was based on a N-N-coupled bis-β-diketiminate ligand (NN), was obtained from the reaction of [NN-(MgnBu) ] with PhSiH. Its crystal structure reveals an almost-tetrahedral arrangement of Mg atoms and two different sets of hydride ions, which give rise to a coupling in the NMR spectrum (J=8.5 Hz). To shed light on the relationship between the cluster size and H release, the thermal decomposition of [NN-(MgH)] and two closely related systems that were based on similar ligands, that is, an octanuclear magnesium hydride cluster and a dimeric magnesium hydride species, have been investigated in detail. A lowering of the H-desorption temperature with decreasing cluster size is observed, in line with previously reported theoretical predictions on (MgH) model systems. Deuterium-labeling studies further demonstrate that the released H solely originates from the oxidative coupling of two hydride ligands and not from other hydrogen sources, such as the β-diketiminate ligands. Analysis of the DFT-computed electron density in [NN-(MgH)] reveals a counterintuitive interaction between two formally closed-shell H ligands that are separated by 3.106 Å. This weak interaction could play an important role in H desorption. Although the molecular product after H release could not be characterized experimentally, DFT calculations on the proposed decomposition product, that is, the low-valence tetranuclear Mg(I) cluster [(NN-Mg)], predict a structure with two almost-parallel, localized Mg-Mg bonds. As in a previously reported β-diketiminate Mg dimer, the Mg-Mg bond is not characterized by a bond critical point, but instead displays a local maximum of electron density midway between the atoms, that is, a non-nuclear attractor (NNA). Interestingly, both of the NNAs in [(NN-Mg)] are connected through a bond path that suggests that there is bonding between all four Mg atoms. Size matters: The temperature that is required for the elimination of H in magnesium hydride clusters is dependent on the cluster size (see scheme). Detailed experimental and/or theoretical data for magnesium hydride and magnesium(I) clusters are reported. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.